Utility, Limitations, and Future of Non-Human Primates for Dengue Research and Vaccine Development - Sariol, Carlos A.; White, Laura J. (Frontiers in Immunology, 2014)
Dengue is considered the most important emerging, human arboviruses, with worldwide distribution in the tropics. Unfortunately there are no licensed dengue vaccines available or specific antiviral drugs. The development of a dengue vaccine faces unique challenges. The 4 serotypes co-circulate in endemic areas, and pre-existing immunity to one serotype does not protect against infection with other serotypes, and actually may enhance severity of disease. One foremost constraint to test the efficacy of a dengue vaccine is the lack of an animal model that adequately recapitulates the clinical manifestations of a dengue infection in humans. In spite of this limitation, Non Human Primates (NHP) are considered the best available animal model to evaluate dengue vaccine candidates due to their genetic relatedness to humans and their ability to develop a viremia upon infection and a robust immune response similar to that in humans. Therefore, most dengue vaccines candidates are tested in primates before going into clinical trials. In this article we present a comprehensive review of published studies on dengue vaccine evaluations using the NHP model, and discuss critical parameters affecting the usefulness of the model. In the light of recent clinical data, we assess the ability of the NHP model to predict immunological parameters of vaccine performances in humans and discuss parameters that should be further examined as potential correlates of protection. Finally we propose some guidelines towards a more standardized use of the model to maximize its usefulness and to better compare the performance of vaccine candidates from different research groups.